Contextual factors influencing the characteristics of female football players - Griffin, J.; Horan, S.; Keogh, J.; Dodd, K.; Andreatta, M.; Minahan, C. (The Journal of Sports Medicine and Physical Fitness, 2021)
Women`s football participation rates are projected to increase to 60 million worldwide by 2026, doubling the current participation. Growing investment and the increase in research in women`s football has had a positive effect on the level of performance over the last 10 years. The present review aimed to examine the literature on the physical and physiological characteristics of female football players from 2010 to 2019 to reflect the recent changes in professionalism. Characteristics investigated include anthropometry, strength, speed, endurance, power, change of direction and repeated sprint ability. These characteristics are presented in relation to playing position, age and competition-level. Results revealed that goalkeepers (171 cm, 66 kg) and defenders (168 cm, 61 kg) were the tallest and had the greatest body mass, while attackers were the fastest players over 20 m (3.05 s) and 30 m (4.38 s) and midfielders had the highest endurance (55.4 mL/kg/min) (P<0.05). Characteristics tended to improve with age until full biological maturity around 17 to 18 years of age. Competition comparisons demonstrated international players have significantly greater speed, repeated sprint ability, power and endurance characteristics (P<0.05). By identifying influential factors, coaches may be able to optimize their training and physical assessment practices, to better expose players to the required stimulus to develop these characteristics considered crucial to improved performance.